Meta-analysis in a nutshell: Techniques and general findings - Martin Paldam (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
The purpose of this article is to introduce the technique and main findings of meta-analysis to the reader, who is unfamiliar with the field and has the usual objections. A meta-analysis is a quantitative survey of a literature reporting estimates of the same parameter. The funnel showing the distribution of the estimates is normally amazingly wide given their t-ratios. Little of the variation can be explained by the quality of the journal (as measured by its impact factor) or by the estimator used. The funnel has often asymmetries consistent with the most likely priors of the researchers, giving a publication bias.
Keywords: B4; C2; 330; meta-analysis; selection of regressions; publication bias